Efficacy of 1.23% Acidulate Phosphate Fluoride Gel on Tooth Sensitivity during Home Bleaching Treatment - Pedram Pishgahi; Parvin Mirzakoochaki (Isfahan University of Medical Sciences, 2024)
One of the side effects of dental home bleaching is hypersensitivity.This study aimed to assess the efficacy of the application of 1.23% acidulated phosphate fluoride (APF) gel before/after daily home bleaching with carbamide peroxide (CP) on tooth hypersensitivity during 14 days of treatment.Materials & Methods:This randomized controlled clinical trial evaluated 24 patients randomly assigned to three groups (n = 8). Group 1 (control) used 20% CP gel for at least 6 hours per night for 2 weeks. Group 2 (APF-bleaching) used 1.23% APF for 4 minutes before using the CP gel. Group 3 (bleaching-APF) used APF gel for 4 minutes after using the CP gel. The bleaching procedure was the same in all three groups and lasted for 2 weeks. The patients were asked to record the severity of their TH daily using a 0-3 numerical severity scale. Data were analyzed by ANOVA and t-test (α = 0.05).Results:The mean TH score was 1.3 in the control group, 0.65 in APF-bleaching, and 0.5 in bleaching-APF (pvalue = 0.019) group. The mean TH score of the control group was significantly higher than that of the APF-bleaching (p value = 0.028) and bleaching-APF (p value = 0.008) groups. The TH score did not significantly change during the 14-day treatment period in the control or bleaching-APF groups. TH significantly decreased with time in the APF-bleaching group (p value < 0.05).Conclusion:Application of 1.23% APF gel before bleaching significantly decreased the severity of TH due to bleaching with 20% CP but could not completely prevent it